Simulation of LTE-TDD in the HAPS channel - Aws Majeed Al-awadi; Mohammed Jawad Al-dujaili (Institute of Advanced Engineering and Science, 2020)
LTE stands for Long Term Evolution. This technology enhances the data rate and capacity using a new radio interface and an optimized core network. This progress was done to satisfy standards defined for the fourth generation of cellular communications in ITU. LTE has two types of transmission: Frequency Division Duplex (FDD) and Time Division Duplex (TDD). Nowadays, LTE-TDD rapidly Grows and takes place of old fixed cellular communications, like WiMAX. Another upcoming technology in the communication industry is High Amplitude Platform Stations (HAPS). Studying the capability of HAPS as a base station for LTE-TDD is the main purpose of this paper. Simulations have done using HAPS channel and compared to Stanford University Interim (SUI) standard channels for different scenarios. Results were compared to achieve a conclusion on HAPS implementation for LTE-TDD based on BER and data throughput.